Enhanced supported living for people with severe and persistent mental health problems: A qualitative investigation. (6th May 2022) - Barnes, Steven; Carson, Jerome; Gournay, Kevin
Abstract: Supported living has been shown to improve functioning and social inclusion in people with severe and persistent mental health problems, reduce hospitalisation and provide secure accommodation in a population where housing needs are often unmet. Conversely, living in supported accommodation has been depicted by some as depersonalising, marginalising and an ordeal to survive. Discussions regarding housing and support often lack a thorough consideration of individual experiences, with a reliance on quantitative surveys. The question remains how to assure that supported accommodations actually are supportive of the residents' ongoing recovery process. The present study sought to shed light on the experiences of residents in an enhanced supported living service in the United Kingdom. Semi‐structured interviews were conducted with nine residents of the service between July 2020 and February 2021. Transcripts were analysed using thematic analysis and indicated three superordinate themes of experiences considered valuable to residents: (1) support from care staff which was readily available; (2), a sense of community and daily activity offered by the residence and on‐site activities; and (3) the experience of supported living as a stepping‐stone in an ongoing recovery process. Findings indicate the power of comprehensive care with supportive staff, peer‐relations, autonomy and fostering hope in empowering individuals in their ongoing recovery.